Kajian Pengembangan Desa Wisata di Provinsi Bengkulu - Nuor Fahrozi Agus (STIA Bengkulu, 2022)
Tourism villages in the process of tourism development in Bengkulu province present a more dynamic type of tourism expressed through the spirit of